Formation of thymol nanoemulsions with combinations of casein hydrolysates and sucrose stearate. (June 2016) - Su, Dan; Zhong, Qixin
Abstract: Casein hydrolysates (CHs) have the improved emulsifying activity than caseins, and the emulsion stability can be principally improved by co-adsorbing sucrose stearate (SS). The objective of this work was to fabricate thymol nanoemulsions using the combination of CH and SS. CH produced by 10 min pancreatic hydrolysis was used at 2% and mixed with SS to prepare emulsions by shear homogenization and heating at 90 °C for 20 min. Addition of SS from 0 to 1.0% increased the thymol content in nanoemulsions ( d 3, 2 ≈ 50 nm) from 1 to 3%. Excess SS however increased the emulsion turbidity and instability due to its poor solubility at ambient conditions. Heating improved the solubility of SS, strengthened its hydrophobic interactions with CH, and thus greatly improved the emulsion storage stability and the stability at pH 3.0 and 5.0. Therefore, the combination of CH and SS provides a novel approach to prepare nanoemulsions. Highlights: Thymol was emulsified with casein hydrolysates (CHs) and sucrose stearate (SS). The CH-SS combination improved the emulsification capacity, especially after heating. Heating improved the SS solubility and strengthened its interactions with CHs. Transparent nanoemulsions with d3, 2 around 50 nm were stable during 60-day storage. The CH-SS combination improved the nanoemulsion stability at pH 5.0.